High-Elevation Populations of Montane Grasshoppers Exhibit Greater Developmental Plasticity in Response to Seasonal Cues - Smith, Julia M.; Telemeco, Rory S.; Briones Ortiz, Bryan A.; Nufio, César R.; Buckley, Lauren B. (Frontiers in Physiology, 2021)
Populations of insects can differ in how sensitive their development, growth, and performance are to environmental conditions such as temperature and daylength. The environmental sensitivity of development can alter phenology (seasonal timing) and ecology. Warming accelerates development of most populations. However, high-elevation and season-limited populations can exhibit developmental plasticity to either advance or prolong development depending on conditions. High-elevation populations of the montane, early-season, univoltine grasshopper Melanoplus boulderensis exhibit rapid early development and slow late development in warm seasons. We investigate the physiology underlying these field observations by examining how diurnal temperature variation and daylength interact to shape growth, development, and performance of several populations along an elevation gradient. Contrary to our expectation of long days delaying development if temperatures were permissive, populations exhibited similar thermal sensitivities of development under long-day conditions. However, short days accelerated the development of high-elevation populations exposed to high temperature variability. Such plasticity commonly evolves to ensure the completion of a generation and is consistent with field observations but is unexpected for an early-season species that generally completes development before days shorten. Selection to develop rapidly as days shorten late in the season may have occurred at higher elevations than those studied. Notably, accelerated development generally did not decrease body size or alter body shape. Developmental plasticity did not strongly influence thermal tolerance but altered the temperature dependence of performance in complex ways inconsistent with trade-offs of accelerated development. Short days increasing the thermal sensitivity of development for high-elevation and season-limited populations is consistent with field phenology. The results highlight that developmental plasticity at the population level can shapes phenological responses to climate change and these responses will have potential implications for community and ecosystem structure.